(x-3)(2-x)-(x-5)(5+x)=-2x(x-6)-5(x-1) -> rezultatul este 7
Mersiiiiii :3
Răspunsuri la întrebare
Răspuns de
3
(x-3)(2-x)-(x-5)(5+x)=-2x(x-6)-5(x-1)
5x-x²-6-(x²-25)= -2x²+12x-5x+5
5x-2x²+19= -2x²+7x+5
-2x²+2x²+19-5=7x-5x
14=2x ⇒ x=14/2=7
5x-x²-6-(x²-25)= -2x²+12x-5x+5
5x-2x²+19= -2x²+7x+5
-2x²+2x²+19-5=7x-5x
14=2x ⇒ x=14/2=7
Alte întrebări interesante
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă